Chronic venous disease. Part 1: pathophysiology and clinical features. (1st July 2022) - Kumar, Piyush; Khan, Ismat Ara; Das, Anupam; Shah, Hiral
Summary: Chronic venous disease (CVD) is a commonly encountered condition in the dermatology outpatient department. If untreated, CVD may progress to chronic leg ulcer causing serious morbidity to the patient. It also affects the quality of life of the affected patient and contributes to loss of work productivity. The spectrum of clinical manifestations for CVD is myriad, ranging from asymptomatic varicose veins and pigmentation to ulceration and scarring. Awareness of spectrum of clinical presentations is required to identify, diagnose and manage CVD. Long‐standing cases may develop ankle joint stiffness, fixed flexion deformity, periostitis and even Marjolin ulcer. Increased venous hypertension, thought to result from valve incompetence and failure of the calf muscle pump, is central to the pathophysiology of the development of CVD. Tissue oedema, hypoxia and subsequent fibrosis are major immediate contributing factors responsible for the clinical manifestations of CVD. Localized, chronic inflammation is now increasingly being recognized as a key player, directly responsible for stasis dermatitis and hypercoagulable state. The complete ramifications of persistent inflammation in CVD are yet to be understood and serious systemic morbidities such as arterial and cardiac disease are increasingly being recognized in association with CVD. Abstract : Chronic venous disease (CVD) is a commonly encountered disease in dermatology outpatient departments. If untreated, CVD may progress to chronic leg ulcer causing serious morbidity to the patient. Part 1 of this review article focuses on the pathophysiology and clinical features of CVD.